The Geothermal Pipeline - Geo-Heat Center (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1984)
Icelander joins GHC staff. Fort Bidwell district heating Project Operational. Indian Valley Hospital Project completed. Hook-ups continuing for Pagosa Springs district heating. Boise district heating project adds customers. Twin Falls College converts third building to geothermal heating. church building using geothermal heating. Greenhouse construction underway in Animas. Elko district heating system continues expansion. Caliente shallow wells productive. First New York state district heating project to start. City of Klamath Falls district heating system to start. Leaham Hot springs development planned. Philip greenhouse completed. Utah state prison project construction completed